Pop cult : religion and popular music - Till, Rupert (London : Continuum, 2010)
'Pop Cult' investigates the ways in which popular music and its surrounding culture have become a primary site for the location of meaning, belief and identity. It provides an introduction to the history of the interactions of vernacular music and religion, and the role of music in religious culture.
Lost in music : pop cults and new religious movements -- Let's talk about sex : sex cults of popular music -- I want to take you higher : drug cults of popular music -- We could be heroes : personality cults of the sacred popular -- In my beautiful neighbourhood : local cults of popular music -- Even better than the real thing : virtual cults of popular music -- Hope I die before I get old : death cults of popular music -- God is a DJ : possession trance cults of electronic dance music -- Do you believe in rock and roll? Musical cults of the sacred popular.
Includes bibliographical references and index.
Includes discography and filmography.
Keywords: Popular music -- Religious aspects; Popular music -- Social aspects